Critical health response in the time of COVID-19: lessons from the past. (June 2021) - Patel, Rabia Ruby; Monique Graham, Tanya
This article examines the South African government's response to COVID-19 by exploring the strong emphasis that has been placed on South Africans taking personal responsibility for good health outcomes. This emphasis is based on the principles of the traditional Health Belief Model which is a commonly used model in global health systems. More recently, there has been a drive towards other health behaviour change models, like the COM-B model and Behaviour Change Wheel (BCW); nonetheless, these remain entrenched within the principles of individual health responsibility. However, the South African experience with the HIV epidemic serves as a backdrop to demonstrate that holding people personally accountable for health behaviour changes has major pitfalls; health risk is never objective and does not take place outside of subjective experience. This article makes the argument that risk-taking health behaviour change in the South African context has to consider community empowerment and capacity building.